Formulasi Dan Uji Aktivitas Gel Fraksi Aktif Biji Kopi Robusta (Coffea Canephora L.) terhadap Stapylococcus aureus sebagai Terapi Ulkus Diabetik - Putri Diana Br Tarigan; Novitaria Br Sembiring; Muhammad Yunus (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Diabetes mellitus is one of the health problems that deserves attention worldwide. Diabetes mellitus causes complications in various organs of the body. One of the complications of diabetes mellitus for sufferers is the appearance of diabetic wounds or gangrene and ulcers that cause susceptibility to bacterial infections. One of the bacteria that causes diabetic wounds is Staphylococcus aureus, which can be found on the skin surface as normal flora. Objective: This study aims to formulate the active fraction of robusta coffee beans (Coffea Canephora L.) into a gel preparation and evaluate its antibacterial activity against Staphylococcus aureus. Methods: This experimental study involved the extraction of robusta coffee beans with 96% ethanol maceration, phytochemical screening, and fractionation using n-hexane, ethyl acetate, and water solvents. Furthermore, the fraction results were tested using the disk diffusion method to determine the active fraction in robusta coffee beans to be formulated into gel preparations with concentrations of 12.5%, 25%, and 50% and physical stability tests were conducted. Based on the results of the study, the water fraction and gel preparation of robusta coffee beans showed inhibition of antibacterial activity against Staphylococcus aureus, with the greatest inhibition at a concentration of 50%. Therefore, the active fraction gel of robusta coffee beans has the potential as a treatment for diabetic wounds. Organoleptic testing of the gel showed a distinctive honey smell, brown color, and a slightly acidic pH of formula 1.